The Effect of Saline Coolant on Temperature Levels during Decortication with a Midas Rex: An in Vitro Model Using Sheep Cervical Vertebrae - Livingston, Asher; Wang, Tian; Christou, Chris; Pelletier, Matthew H.; Walsh, William R. (Frontiers in Surgery, 2015)
Decortication of bone with a high-speed burr in the absence of coolant may lead to local thermal necrosis and decreased healing ability, which may negatively impact clinical outcome. Little data are available on the impact of applying a coolant during the burring process. This study aims to establish an in vitro model to quantitatively assess peak temperatures during endplate preparation with a high-speed burr. Six sheep cervical vertebrae were dissected and mounted. Both end plates were used to give a total of 12 sites. Two thermocouples were inserted into each vertebra, 2 mm below the end plate surface and a thermal camera set up to measure surface temperature. A 3 mm high-pneumatic speed burr (Midas Rex, Medtronic, Fort Worth, TX, USA) was used to decorticate the bone in a side to side sweeping pattern, using a matchstick burr (M-8/9MH30) with light pressure. This procedure was repeated while dripping saline onto the burr and bone. Data were compared between groups using a Student’s t-test. Application of coolant at the bone–burr interface during decortication resulted in a significant decrease in final temperature. Without coolant, maximum temperatures 2 mm from the surface were not sufficient to cause thermal osteonecrosis, although peak surface temperatures would cause local damage. The use of a high-speed burr provides a quick and an effective method of vertebral end plate preparation. Thermal damage to the bone can be minimized through the use of light pressure and saline coolant. This has implications for any bone preparation performed with a high-speed burr.